La Cour suprême et les communications - Langlois, Raynold (Les Cahiers de droit, 1978)
On November 30th, 1977, the Supreme Court rendered two important decisions which put an end to the provincial claims for jurisdiction on cable distribution undertakings. On January 19, 1978, the Supreme Court rendered a third judgment dealing with provincial consumer protection legislation affecting broadcasting undertakings. These three judgments although flowing from unrelated matters, must be read together. They confirm that the federal power over radiocommunications is exclusive. Any service which is connected thereto such as the distribution of programming by means of cables form and integral part of the broadcasting system and, as a result, falls under the federal power. The fact that the cable distribution service is owned and operated by a different person and that it has its own infrastructure is immaterial. The question is : what is the service being rendered. If, as the Court found in the case, the service is mainly to facilitate the public's assess to broadcasting, then it is an integral part thereof. The Court found, however, that a province could control advertising even where it was destined for broadcasting so long as the regulation was directed at the manufacturer and not the broadcaster. It is unclear, however, whether this power would survive the adoption by Parliament of conflicting legislation on the same subject matter.